Mapping the Readiness and Challenges of the MBKM Policy Implementation: A Systematic Literature Review of Micro and Macro Educational Perspectives : Penelitian - Suwarsito Suwarsito; Viviana Lisma Lestari; Childa Faiza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Merdeka Belajar–Kampus Merdeka (MBKM) policy introduced by Indonesia’s Ministry of Education in 2020 seeks to transform higher education by promoting flexible, student-centered learning through internships, community service, and research. However, its implementation faces significant disparities in institutional readiness and ongoing challenges. This systematic literature review (SLR) examines 20 studies to explore both micro- and macro-level perspectives on MBKM implementation. Findings reveal gaps in educator preparedness, student awareness, institutional policy alignment, and infrastructure support. At the macro level, systemic resistance and limited stakeholder engagement hinder policy uptake. This review proposes a comprehensive framework integrating these perspectives to guide more effective implementation strategies and support national education reform goals.